2010
DOI: 10.1007/s00439-010-0821-8
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide linkage scan and association study of PARL to the expression of LHON families in Thailand

Abstract: Leber hereditary optic neuropathy (LHON) is the most common mitochondrially inherited disease causing blindness, preferentially in young adult males. Most of the patients carry the G11778A mitochondrial DNA (mtDNA) mutation. However, the marked incomplete penetrance and the gender bias indicate some additional genetic and/or environmental factors to disease expression. Herein, we first conducted a genome-wide linkage scan with 400 microsatellite markers in 9 large Thai LHON G11778A pedigrees. Using an affected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(24 citation statements)
references
References 48 publications
0
24
0
Order By: Relevance
“…The numbers of affected LHON patients recruited from pedigrees F1, F9 and F66 were two, two and three respectively. All affected individuals have been diagnosed by an ophthalmologist (WC) and have been confirmed as bearing homoplasmic mtDNA 11778G>A [9], [13], [27]. The characteristics of each patient are summarized in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…The numbers of affected LHON patients recruited from pedigrees F1, F9 and F66 were two, two and three respectively. All affected individuals have been diagnosed by an ophthalmologist (WC) and have been confirmed as bearing homoplasmic mtDNA 11778G>A [9], [13], [27]. The characteristics of each patient are summarized in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…However, the frequency of genotype CT of rs953419 (this SNP was not significant after multiple testing correction in Phasukkijwatana et al (2010)) was higher (P = 0.038) in LHON patients (55.9%) than in the control population (45.7%; Table 1), but the P value changed to 0.114 after the Bonferroni correction. Five haplotypes were constructed based on the three SNPs (rs3749446-rs953419-rs1402000).…”
Section: Resultsmentioning
confidence: 83%
“…However, no nuclear gene or SNP has been identified to explain the riddle of LHON. Recently, by using a genome-wide linkage scan and association study, Phasukkijwatana et al (2010) first reported that two SNPs (rs3749446 and rs1402000) in the PARL gene were associated with the expression of LHON in patients from Thailand. Because of potential limits in that study, these authors called for more studies to confirm their observation (Phasukkijwatana et al 2010).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…62 Single nucleotide polymorphisms of PARL have been associated with glaucoma, LHON, and mutations causing Parkinson's disease. 59,63,64 Altering the fission-fusion balance has profound effects on mitochondrial function and structure. With pharmaceutical or genetic inhibition of fusion, there is a collapse of mitochondrial energy production as mitochondria consume ATP 65 which alters mitochondrial distribution toward fission, 54,66 promoting apoptosis.…”
Section: -51mentioning
confidence: 99%